Pelatihan TOEFL Prediksi “Structure & Written Expression” Bagi Mahasiswa Keperawatan : Pelatihan TOEFL Prediksi “Structure & Written Expression” Bagi Mahasiswa Keperawatan - Mika andika Mika Andika (VIDHEAS: Jurnal Abdimas Multidisiplin, 2023)
Entering the current technological era, language skills are one of the administrative requirements to join or act as a driving force in the economic, educational, social, or cultural fields. This is evidenced by the need for a TOEFL certificate. So people are competing to get a good TOEFL score to meet the requirements at an institution/institution. This is also experienced by nursing students where the TOEFL certificate is one of the administrative requirements that must be fulfilled in order to complete college on campus. However, the obstacles they experience are a lack of understanding of the structure and written expression abilities. So that the purpose of this community service activity is to provide TOEFL training which will increase their understanding. This training has several stages, such as the pretest stage, which aims to measure the extent of understanding in answering TOEFL questions. The material presentation stage is explaining the material/TOEFL questions. In the exercise phase, participants are asked to complete the questions after the material has a presentation. At the posttest stage, participants were asked to answer TOEFL questions that were different from the questions on the pretest. There is an increase in scores after comparing the results of the pretest and posttest that have been carried out so that community service can be said to be effective.